Lessons from nature: biomimetic subwavelength structures for high-performance optics - Brunner, Robert; Spatz, Joachim P. (Laser & photonics reviews, 2012)
In nature, optical structures in the subwavelength range have been evolved over millions of years. For example, in the form of ‘moth-eye’ structures they show a strong anti-reflective effect on the compound eyes of night-active insects and therefore offer a successful protection over predators. In this contribution the advantages and challenges to transfer this natural concept of subwavelength structured optical interfaces to high-end optical systems are discussed. Here, in comparison to alternative conventional multilayer systems, the bioinspired anti-reflective structures offer a wide wavelength range and a broad angle dependency. Additionally, adhesion problems are reduced drastically. Simultaneously to the theoretical consideration of the best profile form of the subwavelength structures, appropriate realization technologies have been developed in recent years, where both top-down and bottom-up approaches have been investigated. Depending on the choice of the structuring technique, anti-reflective subwavelength structures are applicable to a wide spectrum of optical elements ranging from micro-optical components to aspheres for applications in imaging and also illumination setups of high-end optical instruments.